2013
DOI: 10.1080/07399332.2012.684816
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Natural History Study of ME/CFS in the Community

Abstract: In previous qualitative research on Myalgic Encephalomyelitis/chronic fatigue syndrome (ME/CFS), researchers have focused on the experiences of patients with ME/CFS in tertiary care samples, which limit the representativeness of the findings to those with access to health care. This qualitative study examined the natural history of a community-based sample of people with ME/CFS. Participants (n=19) were categorized into persisting, incidence, or remitting groups based on their reported illness status across a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Thus, the recovered experience is still marked as different from the pre‐illness one, as participants report managing the demands they make on themselves, resting and responding to impending symptoms, like Anderson et al . 's () participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the recovered experience is still marked as different from the pre‐illness one, as participants report managing the demands they make on themselves, resting and responding to impending symptoms, like Anderson et al . 's () participants.…”
Section: Discussionmentioning
confidence: 99%
“…The lived experience of ME/CFS has been detailed in previous work (Anderson et al 2014) but there is so far no published material on the lived experience of recovery from the syndrome. While Arroll and Howard (2013) have characterised the process of living with ME in the longer term as 'post-traumatic growth', so far research has tended to focus on symptoms which persist and whose severity continues unabated.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, most studies focus on the experiences of individuals with the illness rather than that of the carers (Anderson, Jason, & Hlavaty, 2014). Ax, Gregg, and Jones (2002) concluded that carers of loved ones with CFS are forced into an attitude of acceptance due to a lack of both options and resources; this state of acceptance was defined as resignation.…”
mentioning
confidence: 99%
“…This group was already highly motivated to correct public misperceptions about CFS, and subsequently helped publicize our evidence that ethnic minorities had higher CFS rates than Caucasians and that CFS rates were not greater among those with higher incomes. Qualitative methods (Anderson, Jason, & Hlavaty, 2014) provided us with a deeper understanding of the interaction of the multiple systems involved in the experiences of the patients, and allowed us to link the connection of illness to the distribution of power and privilege within the medical community (e.g., many patients mentioned that they experienced negative attitudes such as physician minimization of their illness). Thus, our work illustrates how ecologically-oriented, systems research can achieve positive ethical and diversity outcomes by reducing stigma and debunking the myth that CFS was a rare “yuppie flu” illness.…”
Section: Stigma Regarding Chronic Health Conditionsmentioning
confidence: 99%